\(\frac{1-3x}{2x}+\frac{3x-2}{2x-1}+\frac{3x-2}{2x-4x^2}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1-3x}{2x}+\frac{3x-2}{2x-1}+\frac{3x-2}{2x-4x^2}\)
\(=\frac{\left(1-3x\right)\left(2x-1\right)+2x\left(3x-2\right)+2-3x}{2x\left(2x-1\right)}\)
\(=\frac{2x-1-6x^2+3x+6x^2-4x+2-3x}{2x\left(2x-1\right)}\)
\(=\frac{-2x+1}{2x\left(2x-1\right)}\)
\(=-\frac{1}{2x}\)
\(\frac{1-3x}{2x}+\frac{3x-2}{2x-1}+\frac{3x-2}{2x-4x^2}\)
\(=\frac{\left(1-3x\right)\left(2x-1\right)}{2x\left(2x-1\right)}+\frac{2x\left(3x-2\right)}{2x\left(2x-1\right)}-\frac{3x-2}{2x\left(2x-1\right)}\)
\(=\frac{2x-1-6x^2+3x+6x^2-4x-3x+2}{2x\left(2x-1\right)}\)
\(=\frac{-2x+1}{2x\left(2x-1\right)}\)
\(=\frac{-\left(2x-1\right)}{2x\left(2x-1\right)}\)
\(=\frac{-1}{2x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1-3x}{2x}+\frac{3x-2}{2x-1}+\frac{3x-2}{2x-4x^2}\)
\(=\frac{\left(1-3x\right)\left(2x-1\right)+2x\left(3x-2\right)+2-3x}{2x\left(2x-1\right)}\)
\(=\frac{2x-1-6x^2+3x+6x^2-4x+2-3x}{2x\left(2x-1\right)}\)
\(=\frac{-2x+1}{2x\left(x-1\right)}\)
\(=-\frac{1}{2x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{x}-\frac{1}{x+1}=\frac{x+1-x}{x\left(x+1\right)}=\frac{1}{x^2+x}\)
b, \(\frac{1}{xy-x^2}-\frac{1}{y^2-xy}=\frac{y^2-xy-xy+x^2}{\left(xy-x^2\right)\left(y^2-xy\right)}=\frac{x^2+y^2}{xy^3-xyxy-xyxy+x^3y}\)Tu rut gon tiep
c, tt
d, cx r
a) \(\frac{1}{x}-\frac{1}{x+1}=\frac{x+1}{x\left(x+1\right)}-\frac{x}{x\left(x+1\right)}\)
\(=\frac{x+1-x}{x\left(x+1\right)}=\frac{1}{x\left(x+1\right)}\)
b) \(\frac{1}{xy-x^2}-\frac{1}{y^2-xy}=\frac{1}{x\left(y-x\right)}-\frac{1}{y\left(y-x\right)}\)
\(=\frac{y}{xy\left(y-x\right)}-\frac{x}{xy\left(y-x\right)}=\frac{y-x}{xy\left(y-x\right)}=\frac{1}{xy}\)
c) \(\frac{9x-3}{4x-1}-\frac{3x}{1-4x}=\frac{9x-3}{4x-1}+\frac{3x}{4x-1}\)
\(=\frac{9x-3+3x}{4x-1}=\frac{6x-3}{4x-1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3}{2x}+\frac{3x-3}{2x-1}+\frac{2x^2+1}{4x^2-2x}\)
\(=\frac{3}{2x}+\frac{3x-3}{2x-1}+\frac{2x^2+1}{2x\left(2x-1\right)}\)
\(=\frac{3\left(2x-1\right)+2x\left(3x-3\right)+2x^2+1}{2x\left(2x-1\right)}\)
\(=\frac{6x-3+6x^2-6x+2x^2+1}{2x\left(2x-1\right)}\)
\(=\frac{8x^2-2}{2x\left(2x-1\right)}=\frac{2\left(4x^2-1\right)}{2x\left(2x-1\right)}=\frac{\left(2x-1\right)\left(2x+1\right)}{x\left(2x-1\right)}\)
\(=\frac{2x+1}{x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\dfrac{3x+6x^2+2x-4x^2}{\left(1-2x\right)\left(1+2x\right)}\cdot\dfrac{\left(1-2x\right)^2}{x\left(2x+5\right)}\)
\(=\dfrac{1-2x}{1+2x}\)
\(\frac{1-3x}{2x}+\frac{3x-2}{2x-1}+\frac{3x-2}{2x-4x^2}\)
\(=\frac{\left(1-3x\right)\left(2x-1\right)+2x\left(3x-2\right)+2-3x}{2x\left(2x-1\right)}\)
\(=\frac{2x-1-6x^2+3x+6x^2-4x+2-3x}{2x\left(2x-1\right)}\)
\(=\frac{-2x+1}{2x\left(2x-1\right)}\)
\(=-\frac{1}{2x}\)
\(\frac{1-3x}{2x}+\frac{3x-2}{2x-1}+\frac{3x-2}{2x-4x^2}\)
\(=\frac{1-3x}{2x}+\frac{3x-2}{2x-1}-\frac{3x-2}{2x\left(2x-1\right)}\)
\(=\frac{\left(1-3x\right)\left(2x-1\right)+2x\left(3x-2\right)-\left(3x-2\right)}{2x\left(2x-1\right)}\)
\(=\frac{2x-1-6x^2+3x+6x^2-4x-3x+2}{2x\left(2x-1\right)}\)
\(=\frac{-2x+1}{2x\left(2x-1\right)}=\frac{-\left(2x-1\right)}{2x\left(2x-1\right)}=-\frac{1}{2x}\)